Clinical characteristics of Graves' disease following COVID-19 infection or vaccination: a multicenter case-control study - Gokcay Canpolat, Asena; Agbaht, Kemal; Elhan, Atilla Halil; Cesur, Mustafa; Alphan Uc, Ziynet; Akcay, Seckin; Sahin, Mustafa (Tubitak Scientific & Technological Research Council Turkey, 2025)
Background/aim: To describe Graves' Disease (GD) associated with COVID-19 infection (COVID) or its vaccines (VAC) and to compare the clinical presentations, laboratory parameters, and short-term clinical course of the disease among different etiology groups (COVID, VAC, and GD control). Materials and methods: Included in this multicenter matched case-control, retrospective cohort study were 239 patients with newly diagnosed (n = 196) or recurrent GD (n = 43) associated with COVID (n = 79) or VAC (n = 160). Each case was matched (1:1) with a control who had been diagnosed with GD prior to COVID. Results: The median age of the entire group was 42 years (female:male = 137:102). Both the COVID (4.6-fold) and VAC (4.1-fold) groups demonstrated higher TSH receptor antibody (TRAb) titers (p < 0.001) compared with the control group (3.5-fold), as well as a higher proportion of recurrent cases. At baseline, the COVID group had higher free triiodothyronine (fT3) levels than the other groups. Graves orbitopathy (GO) was observed in 60 patients (12.6%), with a higher frequency in classical GD (18.4%). At baseline, the variables associated with thyrotoxicosis severity (defined as fT3 levels) were younger age, higher thyroid gland volume (TGV), and etiology, with the COVID and, to a lesser extent, VAC groups presenting with higher fT3 levels. The variables associated with GO were higher TGV, TRAb titers, and smoking, while no association with etiology was identified. Conclusion: The clinical course was similar in all groups other than in some laboratory findings. Although the frequency of GO associated with COVID and VAC was lower, the proportion of cases with a Clinical Activity Score of >= 3 was higher compared to GD. This pattern suggests a potentially stronger immunologic trigger in these cases.
Keywords: Graves' disease; Graves' orbitopathy; COVID-19 infection; inactivated virus COVID-19 vaccination; mRNA COVID-19 vaccination